2023
DOI: 10.1021/acs.analchem.2c04613
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Detection of Trace Disinfection Byproducts by Ag Nanoprism-Modulated Lanthanide MOFs

Abstract: Disinfection byproducts (DBPs), as an emerging water pollutant, present increasing concern and risk in public health and water safety. Due to their low concentration levels and inherent similarity in molecular structures, sensitive and accurate determination of DBPs is still a challenge especially for onsite or online detection. Herein, a self-regulated fluorescent probe based on the Ag nanoprism-modified lanthanide metal− organic framework (AgNPR@EuMOF) is designed for trichloroacetic acid (TCAA) detection. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 59 publications
0
12
0
Order By: Relevance
“…Recently, Mao et al reported the first monochrome fluorescence sensor for trichloroacetic acid detection. 9 However, due to the singularity of its output color and the diversity of HAAs, it is urgent to develop a more universal multicolor fluorimetry method.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Mao et al reported the first monochrome fluorescence sensor for trichloroacetic acid detection. 9 However, due to the singularity of its output color and the diversity of HAAs, it is urgent to develop a more universal multicolor fluorimetry method.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Of all available approaches, fluorimetry, for its facile operability, high sensitivity, and rapid response, may be an ideal candidate method for the HAA assay. Recently, Mao et al reported the first monochrome fluorescence sensor for trichloroacetic acid detection . However, due to the singularity of its output color and the diversity of HAAs, it is urgent to develop a more universal multicolor fluorimetry method.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, PGM nanostructures are more catalytically active than most other types of peroxidase mimics. 21,22 PGM nanostructures have exceptional resistance to oxidation and high temperatures, which contributes to their outstanding chemical and thermal stabilities. They can be conveniently functionalized with bioreceptors through noncovalent and/or covalent methods.…”
Section: Introductionmentioning
confidence: 99%
“…Wang and his team designed a dual-emitting Ln-MOF fluorescent sensor for discriminative analysis of structurally similar antibiotics . Fang et al utilized the unique luminescent properties of the EuMOF sensor for TCAA detection . In addition to having the advantages of general MOF materials, conductive metal–organic frameworks (C-MOFs) have attracted great attention benefitting from their high conductivity. Yang and his team prepared a conductive bimetallic MOF (NiCo-HHTP) to improve ECL performance by increasing conductivity, opening a new chapter for designing highly conductive MOF-based ECL materials .…”
mentioning
confidence: 99%